Comparison of calibration methods for accelerometers used in human motion analysis. Issue 11 (November 2016) - Nez, Alexis; Fradet, Laetitia; Laguillaumie, Pierre; Monnet, Tony; Lacouture, Patrick
Highlights: A review of measurement models and calibration methods for accelerometers is presented. Measurement models and calibration methods are evaluated. Useful recommendations for better selection of a calibration process are provided. Calibration using a precise alignment installation offers the best accuracy. Abstract: In the fields of medicine and biomechanics, MEMS accelerometers are increasingly used to perform activity recognition by directly measuring acceleration; to calculate speed and position by numerical integration of the signal; or to estimate the orientation of body parts in combination with gyroscopes. For some of these applications, a highly accurate estimation of the acceleration is required. Many authors suggest improving result accuracy by updating sensor calibration parameters. Yet navigating the vast array of published calibration methods can be confusing. In this context, this paper reviews and evaluates the main measurement models and calibration methods. It also gives useful recommendations for better selection of a calibration process with regard to a specific application, which boils down to a compromise between accuracy, required installation, algorithm complexity, and time.